Acute myocardial infarction risk factors at radiation-dangerous workplaces - Yu. V. Semenova; A. B. Karpov; T. M. Litvinenko; R. M. Takhauov; V. P. Leonov (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To study risk factors (RF) of acute myocardial infarction (AMI), their significance and interplay in a “closed” population – people with chronic low-dose ionizing radiation (IR) exposure at their workplace. Material and methods. According to WHO AMI Registry, 1 370 AMI cases were analyzed, including 327 cases in people exposed to long-term low-dose IR at their workplace. A prospective cohort study of AMI morbidity in a “closed” population (1998-2002) was performed. Results. It was demonstrated that total dose of external radiation, duration of working in radiation-dangerous environment, and traditional cardiovascular RF, were independently distributed in IR-exposed AMI patients. Maximal total doses of external radiation were registered in young AMI patients. Individual dose negatively correlated with arterial hypertension (AH) duration before AMI development. Conclusion. Among persons with long-term IR exposure, psycho-emotional stress, smoking, and AH were the leading cardiovascular RF in AMI pathogenesis. Long-term, low-dose IR enhanced traditional cardiovascular RF (dyslipidemia, AH) aggression in AMI pathogenesis.